Mapping habitat suitability and connectivity for Himalayan brown bears in Pakistan: Implications for conservation management - Shoaib Hameed; Shakeel Ahmad; Jaffar Ud Din; Hussain Ali; Muhammad Younas; Muhammad Kabir; Niloufar Lorestani; Sarwat Jahan; Muhammad Ali Nawaz (Global Ecology and Conservation)
The Himalayan brown bear (Ursus arctos isabellinus) is a subspecies of brown bear that represents an ancient lineage. In Pakistan, it is classified as a critically endangered species with a patchy distribution, surviving in isolated populations over an area of about 150,000 km2. Information on the habitat requirements of the brown bear is scarce in Asia. This study aims to construct country-wide habitat suitability and identify movement corridors to inform policies that strengthen connectivity among patches. Empirical data were collected over an area of 31,000 km² of the species' historic range in Pakistan. A habitat suitability map was generated utilizing an ensemble approach. The model predicted suitable habitat for brown bears spanning 54,885 km², which retains only about one-third of their former range. The main predictors for brown bear habitat suitability were the annual temperature range, the maximum temperature of the warmest month, and precipitation seasonality. Twenty-eight percent of the suitable habitat falls within existing higher-degree protected areas and national parks. However, some good patches remain unprotected or are protected to a lower degree. The connectivity model indicates that the population in the Hindu Kush range is isolated. The brown bear populations in the Pamir-Karakoram range appear to be connected to those in China and Afghanistan, while the Himalayan population has a weak connection with the population in India. We recommend validating movement corridors by tracking individuals via telemetry or genetic methods. Efficient management of existing protected areas and the expansion of protection to include unprotected habitats identified in this study is essential for safeguarding the future of Himalayan brown bears in Pakistan.